Self-adapting epidemic broadcast algorithms - Rodrigues, Luís (2004)
Epidemic broadcast algorithms have a number of characteristics, such as strong resilience to node failures, that make them an appealing technology to build survivable systems. However, the performance of existing protocols is highly dependent of runtime parameters, such as the network load or network topology. In the current extended abstract we advocate, using concrete illustrations, the use of self-adapting epidemic broadcast algorithms.